2013
DOI: 10.1093/gji/ggt458
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters and radiation efficiency for intermediate-depth earthquakes in Northeast Japan

Abstract: We estimated source parameters of 216 intermediate-depth (65-150 km) earthquakes (M w 4.0-7.0) in the Pacific slab beneath Japan along using Hi-net data. We made determinations of static stress drop, radiated energy and radiation efficiency, along with estimates of the whole path attenuation, to study the source scaling as a function of earthquake size and depth. Our results show that there is a small increase in the values of the ratio of radiated energy to seismic moment, as a function of seismic moment, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
7
19
0
Order By: Relevance
“…The mean stress drops for both regions range from around 16–60 MPa (somewhere between 20 and 30 MPa for most data selection tests). These values for the Hokkaido region are in agreement with previous results from Kita and Katsumata () and from Nishitsuji and Mori (). We find no significant variation of stress drop with depth for either single region, though it must be noted that we have confined our study to earthquakes in a narrow depth range (see, e.g., Figures S9 and S10).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The mean stress drops for both regions range from around 16–60 MPa (somewhere between 20 and 30 MPa for most data selection tests). These values for the Hokkaido region are in agreement with previous results from Kita and Katsumata () and from Nishitsuji and Mori (). We find no significant variation of stress drop with depth for either single region, though it must be noted that we have confined our study to earthquakes in a narrow depth range (see, e.g., Figures S9 and S10).…”
Section: Resultssupporting
confidence: 93%
“…Plotting the radiated efficiency (Figures and ), however, shows a large scatter with no clear trend, perhaps a minor decrease in stress drop with moment for the Hokkaido data set that is not statistically significant (it is difficult to regress a line). The majority of radiated efficiencies (Figures and ) range from 0.04 to about 0.11 for the Brune model tests, which is lower than for shallow events, and consistent with the general observations of intraslab earthquakes (Ko & Kuo, ; Nishitsuji & Mori, ). There is not a significant difference in the radiated efficiency between the two regions, nor, as mentioned, is there any significant trend with moment.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The stress drop shows a slight increase as a function of moment, given by the equation Δσ~M00.190.5emprefix±0.5em0.02. The scaling of stress drop is in agreement with previous work on intermediate‐depth earthquakes [ Prieto et al ., ; Nishitsuji and Mori , ] and comes naturally from the moment scaling of rupture duration observed for deep earthquakes. The apparent stress also increases as σA~M00.20.5emprefix±0.5em0.02.…”
Section: Average Rupture Propertiesmentioning
confidence: 99%
“…Thermal shear runaway in the focal region can generate highly localized ductile deformation and slip instabilities (Kanamori et al, 1998;Prieto et al, 2012). Recently, local and global seismological studies have shown that most of IDEs have a low radiation efficiency, suggesting that thermal shear runaway is the leading source mechanism of IDEs (Díaz-Mojica et al, 2014;Nishitsuji & Mori, 2013;Prieto et al, 2013Prieto et al, , 2017. Recently, local and global seismological studies have shown that most of IDEs have a low radiation efficiency, suggesting that thermal shear runaway is the leading source mechanism of IDEs (Díaz-Mojica et al, 2014;Nishitsuji & Mori, 2013;Prieto et al, 2013Prieto et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%